The Potential of Sea Urchin (Diadema Setosum) Extracts as Antibacterial Against Staphylococcus Aureus - Hardani, Hardani; Sukmana, Dhika Juliana; Atfal, Bustanul (Trends in Sciences, 2023)
Secondary metabolites from sea urchin shells contain active substances with the potential of antibiotics. The purpose of this study was to investigate how sea urchin shell extract affected the development of the Staphylococcus bacterium. In this kind of research, the active chemical content of sea urchin shell extract was examined quantitatively, using scanning electron microscope (SEM) and Fourier Transform Infrared (FTIR), as well as the extract’s effect on the development of Staphylococcus aureus bacteria. According to the study, the average level of total flavonoids was 1.29 %, total alkaloids were 0.12 %, and total tannins were 1.0 %. Sea urchin shell powder has an absorbance of 0.42 at a wavelength of 1,400.84 cm–1. According to microbiological experiments, sea urchin shell ethyl acetate extract was able to stop Staphylococcus aureus growth in the category of the strong inhibition zone (inhibition zone diameter of 12 mm). Extract from sea urchin shells has antibacterial properties and may be used to make anti-diabetic ointments. This fabrication is a fantastic option for use in healthcare and medicine. HIGHLIGHTS In this study, there are several main points including: The objective of this research is to determine the antibacterial activity of sea urchin shell extracts with various solvents. FTIR and SEM results to determine the particle size of sea urchin shell powder and the compounds contained therein. Based on the results of the proximate test to see the antioxidant activity of the extract, it is known that the ethyl acetate extract contains the most flavonoid extract (1.6 %w/w). Ethyl acetate extract can inhibit the growth of Staphylococcus aureus bacteria in the Strong inhibition category. GRAPHICAL ABSTRACT